Learning from differences: a strategy for teacher development in respect to student diversity. Issue 1 (2nd January 2016) - Messiou, Kyriaki; Ainscow, Mel; Echeita, Gerardo; Goldrick, Sue; Hope, Max; Paes, Isabel; Sandoval, Marta; Simon, Cecilia; Vitorino, Teresa
Abstract : Drawing on evidence gathered as a result of collaborative action research carried out in 8 secondary schools in 3 European countries, this paper proposes an innovative strategy for helping teachers respond positively to learner diversity. The strategy merges the idea of lesson study with an emphasis on listening to the views of students. The research suggests that it is this latter emphasis that makes the difference as far as responding to learner diversity is concerned. It is this that brings a critical edge to the process that has the potential to challenge teachers to go beyond the sharing of existing practices in order to invent new possibilities for engaging students in their lessons. The paper also considers some of the difficulties involved in using this strategy.